Subsídios para a história da educação no Brasil: um estudo da revista do Instituto Histórico e Geográfico de São Paulo - Pereira, Maria Aparecida (2013)
This thesis aims to analyze the contributions of the Journal of the Institute of History and Geography of São Paulo (RIHGSP) for history of Brazilian education through an analysis of articles published in this journal between 1895 and 2004. The motivation for the study came from the fact that despite the importance of Geographical and Historical Institutes for national historiography, which can be proven by numerous academic studies conducted, there is a gap in the historiography of Brazilian education regarding the use of these journals institutes as primary sources for the history of education. Therefore, this thesis aims to answer the following research question: what are the contributions of RIHGSP for the History of Education in Brazil? The justification for this research is grounded in the understanding that the study of scientific production in the pages of this magazine is relevant to the reconstruction of their own national historiography and to demonstrate the role that information sources play in dissemination of information and the development of the research scientific education. Thus , the main objective of the research was to highlight the contributions of RIHGSP to the historiography of Brazilian education , and the specific objectives were : a) outline a historical overview of Geographical and Historical Institutes in national and world stage standing in this context the History Institute and Geography of São Paulo , b ) describe the main features of the Journal of the Historical and Geographical Institute of São Paulo ( RIHGSP) c ) analyze this scientific production according to bibliometric parameters of authorship, thematic and temporal distribution; d) conduct a content analysis of a selected sample of 20 articles RIHGSP related to the theme of the history of education. From the methodological point of view the research was characterized as an exploratory and descriptive study. The analytical approaches were supported in the bibliometric analysis and content analysis and involved the following steps: literature review, collection, organization and systematization of data and analysis and interpretation of results. Thus, it was possible to obtain scientific evidence to demonstrate that the texts published in RIHGSP, are key to the history and historiography of Brazilian education, because they allow understanding how the literate elite - represented by intellectuals who publish articles in this journal - thought education Brazilian.